ANALISIS ELEMEN FASAD ARSITEKTUR MODENEN TROPIS PADA PERANCANGAN RESTORAN DAN BUTIK DI SAMARINDA - Thamrin, Nur Husniah; Anjani, Nyi Laras Bunga; Anila, Chaeria (Indonesian Society of Applied Science, 2025)
The development of the culinary and fashion sectors in Samarinda has increased the demand for building designs that adapt to the city's hot and humid tropical climate. Modern tropical architecture is a relevant approach for designing restaurants and boutiques, emphasizing energy efficiency and thermal comfort. This study analyzes the façade elements of a restaurant and boutique in Samarinda using a qualitative descriptive method through field observations and theoretical studies. The façade design of LA Restaurant and Boutique in Samarinda incorporates modern tropical elements such as sloped roofs, canopies, wooden and vegetative secondary skins, and large glass openings to optimize natural lighting and cross ventilation. Semi-outdoor spaces with rooftop gardens and climbing vegetation enhance thermal comfort and the building’s aesthetic appeal. The findings indicate that the combination of these façade elements achieves a balance between functionality, sustainability, and visual attractiveness within the context of modern tropical architecture. Key words: modern tropical , architecture, façade, restaurant, boutique